Between terror and tolerance : religious leaders, conflict, and peacemaking - Sisk, Timothy D., 1960- (UPCC book collections on Project MUSE., 2011)
Civil war and conflict within countries is the most prevalent threat to peace and security in the opening decades of the twenty-first century. A pivotal factor in the escalation of tensions to open conflict is the role of elites in exacerbating tensions along identity lines by giving the ideological justification, moral reasoning, and call to violence. Between Terror and Tolerance examines the varied roles of religious leaders in societies deeply divided by ethnic, racial, or religious conflict. The chapters in this book explore cases when religious leaders have justified or catalyzed violence.